1989
DOI: 10.1111/j.1651-2227.1989.tb11092.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Behavioural State on Blood Pressure in Preterm Infants during the First 5 Days of Life

Abstract: The influence of behavioural state on neonatal blood pressure was studied in 19 healthy preterm infants. During the first five days of life every three hours a series of oscillometric blood pressure measurements was made. During the measurements the behavioural state was scored. The predominant states were quiet and active sleep. We confirmed the age-dependency of blood pressure with a steep increase during the first day of life. After the first day blood pressure and heart rate were slightly higher when the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…43 Infant BP is higher when awake and crying, when feeding or sucking, and when being held head up. 50,51 The standardized protocol for BP measurement studied by Nwankwo et al is in line with the findings of our systematic review. 43 For oscillometric BP measurements, an appropriate sized cuff should be applied to the right upper arm, the neonate allowed to settle and when the infant is asleep or quietly awake, up to 3 BP measurements should be taken.…”
Section: Discussionsupporting
confidence: 89%
“…43 Infant BP is higher when awake and crying, when feeding or sucking, and when being held head up. 50,51 The standardized protocol for BP measurement studied by Nwankwo et al is in line with the findings of our systematic review. 43 For oscillometric BP measurements, an appropriate sized cuff should be applied to the right upper arm, the neonate allowed to settle and when the infant is asleep or quietly awake, up to 3 BP measurements should be taken.…”
Section: Discussionsupporting
confidence: 89%
“…Positioning did not affect the drowsy and awake states which collectively occurred only 1·4% of the time during prone placement and 4% during supine. Van Ravenswaaij‐Arts et al . (1989) found that quiet and active sleep were the prominent states and the awake state occurred less than 22% of the time in healthy preterm infants younger than 36 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…1991). Quiet and active sleep were also distinguished among preterm infants of 26–28 weeks gestation (Karch et al . 1982, Van Ravenswaaij‐Arts et al .…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation